Mechanism of Porcine Liver Xanthine Oxidoreductase Mediated N-Oxide Reduction of Cyadox as Revealed by Docking and Mutagenesis Studies - Chen, Chigang (Public Library of Science, 2013)
Xanthine oxidoreductase (XOR) is a cytoplasmic molybdenum-containing oxidoreductase, catalyzing both endogenous purines and exogenous compounds. It is suggested that XOR in porcine hepatocytes catalyzes the N-oxide reduction of quinoxaline 1,4-di-N-oxides (QdNOs). To elucidate the molecular mechanism underlying this metabolism, the cDNA of porcine XOR was cloned and heterologously expressed in Spodoptera frugiperda insect cells. The bovine XOR, showing sequence identity of 91% to porcine XOR, was employed as template for homology modeling. By docking cyadox, a representative compound of QdNOs, into porcine XOR model, eight amino acid residues, Gly47, Asn352, Ser360, Arg427, Asp430, Asp431, Ser1227 and Lys1230, were located at distances of less than 4Å to cyadox. Site-directed mutagenesis was performed to analyze their catalytic functions. Compared with wild type porcine XOR, G47A, S360P, D431A, S1227A, and K1230A displayed altered kinetic parameters in cyadox reduction, similarly to that in xanthine oxidation, indicating these mutations influenced electron-donating process of xanthine before subsequent electron transfer to cyadox to fulfill the N-oxide reduction. Differently, R427E and D430H, both located in the 424–434 loop, exhibited a much lower K(m) and a decreased V(max) respectively in cyadox reduction. Arg427 may be related to the substrate binding of porcine XOR to cyadox, and Asp430 is suggested to be involved in the transfer of electron to cyadox. This study initially reveals the possible catalytic mechanism of porcine XOR in cyadox metabolism, providing with novel insights into the structure-function relationship of XOR in the reduction of exogenous di-N-oxides.